15 Amazing--and--free--Google lab projects you never knew existed. - Ion, Florence (Mac life)
Whether you're sending email in Gmail, getting Maps, or pretending to be part of the latest microblogging craze with Google Buzz, the G-world is everywhere. Well, hang on to your tinfoil hat because it turns out this Google thing goes deep--way deep. The G-Men have an entire library of web applications and services stacked up behind the everyday heavy hitters you may have come to take for granted. Some of them are secretly tucked away behind a door in the Google Labs, but all of them--even the ones wearing their Public Beta scrubs--are readily available to play with, not to mention absolutely free.